Foliar application of benzovindiflupyr shows non‐fungicidal effects in wheat plants. Issue 3 (4th December 2017) - Kuznetsov, Dmitry; Cazenave, Alexandre Brice; Rambach, Odile; Camblin, Philippe; Nina, Mafalda; Leipner, Jörg
Abstract: BACKGROUND: The fungicide benzovindiflupyr belongs to the class of succinate dehydrogenase inhibitors (SDHIs). Certain SDHIs have shown plant physiological effects, so‐called secondary effects, that appeared to be related to the plant water status. Therefore, the effect of benzovindiflupyr on transpiration of leaves and whole wheat plants was studied under controlled conditions. Furthermore, wheat yield trials under controlled and natural drought stress in the field were conducted. RESULTS: Transpiration of detached wheat leaves was reduced by benzovindiflupyr in a dose‐dependent manner. Similarly, whole‐plant transpiration decreased for several days following application of this fungicide. In 16 field trials under drought stress conditions that were classified as disease‐free, treatment of wheat plants at the flag leaf stage or at heading with benzovindiflupyr showed a grain yield increase (+5.2%; P ≤ 0.01) that was partially attributed to an increased thousand‐grain weight. CONCLUSIONS: Water saving during pre‐anthesis as a result of benzovindiflupyr application may be associated with better seed setting and filling under dry field conditions in wheat. The results of this research provide new insights into secondary effects of SDHIs that lead directly to yield improvements. © 2017 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Secondary effects of the SDHI fungicide benzovindiflupyr were studied in wheat. The product decreased plant transpiration and increased grain yield in disease free field trials under drought stress.